Characteristics of Anode Materials for Nickel Electroforming. Issue 9 (1st September 2022) - Green, T. A.; Tambe, C. Enowmbi; Roy, S.
Abstract : This study comprised an investigation of the characteristics of commercial nickel anode materials routinely employed in sulfamate-based electroforming processes. These included examples of sulfur depolarised anodes containing a relatively high sulfur content and those with much lower levels. Electrochemical studies indicate that the sulfur depolarised anodes underwent dissolution in the active region and were capable of sustaining large current densities at low potentials without passivating, and with current efficiencies approaching 100%. In contrast, low-sulfur containing anodes could only sustain low current densities in the active region, and were prone to passivation. These materials could only undergo high rate dissolution in the transpassive region, but this required relatively high anode potentials and was accompanied by various side reactions which lowered the current efficiency. Additional studies were performed to characterise the sulfamate oxidation products which generates a distinct UV absorption band at 245 nm. These species were produced only when low-sulfur content or inert (platinum) anodes were used, and were absent when sulfur depolarised anodes were employed. The principal anode product was azodisulfonate, but trace amounts of other sulfonate species and sulfur-containing anions may also be present.